Design and Research on Full Bolt Connected Box Beam-Column Joints of Cantilever Short Beams with Attachments Connecting Plate. Issue 1 (November 2020) - Wang, Xiaobo; Yan, Yajie
Abstract: Aiming at the assembly connection of box beams and columns, this paper proposes a connection that can realize rapid on-site assembly. The joint is mainly composed of two parts, a box-shaped column welded with a short cantilever beam and structural reinforcement measures and a box-shaped beam attached with connecting plates. The connecting plates are used as accessories of the box beam and shipped with the box beam. When installing, the outer connecting plate is rotated by 180° to the designated position, the inner connecting plate is slid into the designated position, and then these members including the box beam and the short cantilever beam are connected by bolts. The joint is simple and easy to install. It can not only realize rapid assembly on site, but also transmit force directly and reliably. It is an excellent joint for assembled steel structure.